2018
DOI: 10.1007/s00384-018-3091-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of distant metastasis sites and surgery in stage IV colorectal cancer: a population-based study

Abstract: The metastatic site was an independent prognostic factor in stage IV colorectal cancer. Also, carefully chosen patients may benefit from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 27 publications
9
47
1
Order By: Relevance
“…Patients with CRC-PM who were submitted to local treatments combined with chemotherapy or chemotherapy alone for pulmonary metastases were included in our study. Our data showed that the 3-year overall survival rate of 119 patients was 51.2%, and the 5-year overall survival rate was 39.7%, which was consistent with the previous literature [8]. Previous studies had mostly focused on the patients undergoing resection of the lung metastases and patients who did not receive lung metastasectomy were excluded.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with CRC-PM who were submitted to local treatments combined with chemotherapy or chemotherapy alone for pulmonary metastases were included in our study. Our data showed that the 3-year overall survival rate of 119 patients was 51.2%, and the 5-year overall survival rate was 39.7%, which was consistent with the previous literature [8]. Previous studies had mostly focused on the patients undergoing resection of the lung metastases and patients who did not receive lung metastasectomy were excluded.…”
Section: Discussionsupporting
confidence: 91%
“…However, in this Danish cohort study the benefit for lung metastasectomy was only found in univariate analyses and non-significant benefit was seen at their multivariate analysis for lung metastasectomy, hence selection bias (healthier patients with less metastatic disease, and better biology get operated) is inherent. Luo et colleagues [37] demonstrated in their SEER database analysis that the metastatic site of patients with mCRC has prognostic impact. Indeed, isolated liver metastases have a better prognosis compared to metastases at multiple sites.…”
Section: National Comprehensive Cancer Network (Nccn) Andmentioning
confidence: 99%
“…46 In a recent review of 8361 patients from 21 studies, 5-year survival rates after the first PM were 24% to as high as 82%, and median survival ranged from 35 to 70 months. 14 49 This study demonstrated that a significant survival benefit was observed for patients who underwent resection of liver and lung metastases. In addition, in patients who underwent resection of both primary and metastatic lesions, those with isolated lung metastases showed better overall survival than isolated liver metastases.…”
Section: Surgical Outcomes and Prognostic Indicatorsmentioning
confidence: 81%
“…An analysis of 15 studies, all including at least 50 patients undergoing PM for CRC with curative intent and totaling 1669 patients, demonstrated a mean 5‐year overall survival of 49%, and a median 5‐year overall survival of 45% with a range of 25% to 72% . A recent analysis of the Surveillance, Epidemiology, and End results (SEER) database found that patients with isolated lung metastases from CRC had a median survival of 20 months, with significantly improved cancer‐specific and overall survival compared with other sites of metastasis . This study demonstrated that a significant survival benefit was observed for patients who underwent resection of liver and lung metastases.…”
Section: Surgical Outcomes and Prognostic Indicatorsmentioning
confidence: 99%